La dissonance communicationnelle des « porteurs de l’alerte » climatique - Lionel Scotto d’Apollonia (Éditions en environnement VertigO, 2016)
This paper analyses french climatologists’ communication, about their committed in global warming controversies. It presents a part of outcomes of a socioepistemic analysis on global warming controversies. It lights discursive strategies of researchers, who adopt more or less expert and/or political posture depending on different forums. This paper is based on a specific non-reductionist epistemological framework built specifically for socioscientific controversies such as climate change, which mobilizing different sociological fields sometimes controversial. In a first part this paper provides an inventory of a few socio-historical trajectories of the main contentious issues in the scientific literature with peer-reviewing. The second part analyzes communication of researchers focusing on the concept of "uncertainty". The paper demonstrates that some climatologists’ discourses climate "alarm carriers" reveal a form of communicative dissonance reflecting a tension between their own ethics "belief" (the science) and the "responsibility" (talk the risk they perceive). In conclusion, this paper contributes to the debate in the case of environmental controversies about the evolution of relationship between sciences-society and discusses the heuristic perspective of science so called "post-normal".